1988
DOI: 10.1128/jb.170.1.213-217.1988
|View full text |Cite
|
Sign up to set email alerts
|

Formate-nitrate respiration in Salmonella typhimurium: studies of two rha-linked fdn genes

Abstract: Localized mutagenesis was used to obtain rha-linked mutations in Salmonella typhimurium, resulting in defects in the nitrate reductase-linked formate dehydrogenase (FDHN). Thefdn mutants obtained fell into two groups which differed in several respects. Group I isolates lacked FDHN activity under all conditions examined and exhibited wild-type levels of the hydrogenase-linked formate dehydrogenase (FDHH). Group II isolates appeared defective in FDHN only when freshly prepared extracts were assayed; restoration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
12
2
Order By: Relevance
“…Indeed, we originally identified our fdhD+ plasmids on the basis of their complementation patterns in the S. typhimurium mutants; subsequent comparison of our plasmids with those of Schlindwein et al (28) (Table 3). Finally, it has been suggested that fdnB encoded a structural component of cyt bFd, (26). However, our analysis of the fdnGHI operon of E. coli has shown that the structural gene for this cytochrome is encoded byfdnI (4,5 Table 2).…”
Section: Mo)mentioning
confidence: 67%
See 4 more Smart Citations
“…Indeed, we originally identified our fdhD+ plasmids on the basis of their complementation patterns in the S. typhimurium mutants; subsequent comparison of our plasmids with those of Schlindwein et al (28) (Table 3). Finally, it has been suggested that fdnB encoded a structural component of cyt bFd, (26). However, our analysis of the fdnGHI operon of E. coli has shown that the structural gene for this cytochrome is encoded byfdnI (4,5 Table 2).…”
Section: Mo)mentioning
confidence: 67%
“…As VJS691 but X(4fdnG-laCZ)UGA (2,3,20,26). We used MacConkey-nitrate medium to screen TnJO-mutagenized colonies of E. coli.…”
Section: Mo)mentioning
confidence: 99%
See 3 more Smart Citations